Sustained micellar delivery via inducible transitions in nanostructure morphology - Karabin, Nicholas B.; Allen, Sean; Kwon, Ha-Kyung; Bobbala, Sharan; Firlar, Emre; Shokuhfar, Tolou; Shull, Kenneth R.; Scott, Evan A. (Nature communications, 2018)
Nanocarrier administration has primarily been restricted to intermittent bolus injections with limited available options for sustained delivery in vivo. Here, we demonstrate that cylinder-to-sphere transitions of self-assembled filomicelle (FM) scaffolds can be employed for sustained delivery of monodisperse micellar nanocarriers with improved bioresorptive capacity and modularity for customization. Modular assembly of FMs from diverse block copolymer (BCP) chemistries allows in situ gelation into hydrogel scaffolds following subcutaneous injection into mice. Upon photo-oxidation or physiological oxidation, molecular payloads within FMs transfer to micellar vehicles during the morphological transition, as verified in vitro by electron microscopy and in vivo by flow cytometry. FMs composed of multiple distinct BCP fluorescent conjugates permit multimodal analysis of the scaffold’s non-inflammatory bioresorption and micellar delivery to immune cell populations for one month. These scaffolds exhibit highly efficient bioresorption wherein all components participate in retention and transport of therapeutics, presenting previously unexplored mechanisms for controlled nanocarrier delivery. Nanocarrier administration is often performed via intermittent bolus injection while sustained delivery platforms are rarely reported. Here the authors demonstrate that the cylinder-to-sphere transitions of self-assembled filomicelle scaffolds can be used for sustained delivery with improved resorptive capacity and biocompatibility.